Auditor’s role in corporate scandals - Rozhnova, Ekaterina; Králíček, Vladimír, 1952-; Jurka, Robert; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
This thesis aims to examine the extent of the auditors’ role in corporate scandals, specifically their responsibilities for fraud detection. To achieve the thesis's purpose and goals, a literature review was conducted, where 47 academic articles and research papers were gathered, analysed, and split into categories based on the ideas and contributions illustrated in the contents of these papers. The findings revealed four main categories of concerns on the auditor’s role and responsibility in corporate scandals and fraud detection that are 1) fraud detection, 2) auditing methods, 3) education, expertise, training, and 4) auditor’s responsibility. The notions illustrated in the results correspond with the prior theoretical background. Fraud detection is observed to be the auditor's partial and not primary responsibility, despite the continuous increase in the scope of procedure and responsibilities for fraud detection. Fraud detection is stated to be an elaborate task, as the fraudster conceals fraud and purposefully aims to deceive the auditor. Moreover, fraud detection by the auditor is a rare event. In addition, the expectation gap of auditors’ responsibility is present. Therefore, the major concern of results from the literature review was focusing on the importance of education and training of the auditor, and consideration of adding a fraud specialist or integrating forensic accounting into the curriculum, as well as the integrating modern technological advances, such as data mining or machine learning, to the audit process. Furthermore, the results exhibited deliberation on the various auditing methods which can improve fraud detection and the improvement of the language of the regulations to provide the guidance with more clarity and redress the expectation gap as well as increase the efficiency of the auditors.
Vedoucí práce: Vladimír Králíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses